Appraising the economics of smart meters : costs and benefits - Torriti, Jacopo (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"This book focuses on the economics of smart meters and is one of the first to present comprehensive evidence on the impacts, cost-benefits and risks associated with smart metering. Throughout this volume, Jacopo Torriti integrates his findings from institutional cost-benefit analyses and smart metering trials in a range of European countries with key economic and social concepts and policy insights derived from almost ten years of research in this area. He explores the extent to which the benefits of smart meters outweigh the cost, and poses key questions including: which energy savings can be expected from the roll out of smart meters in households? Is Cost-Benefit Analysis an appropriate economic tool for assessing the impacts of smart metering rollouts? Can smart meters play a significant role in research on people's activities and the timing of energy demand? Torriti concludes by providing a much-needed survey of recent changes and expected future developments in this growing field. This book will be of great interest to students and scholars of energy policy and demand and smart metering infrastructure"--
OCLC-licensed vendor bibliographic record.
Keywords: Recording electric meters -- Cost effectiveness; Electric power production -- Costs; Electric power consumption; TECHNOLOGY / Environmental Engineering & Technology; BUSINESS & ECONOMICS / Economics / Comparative